could some one help me with this pre-calc question please ? Logarithms and their properties 3/2/2014 | Vanessa from Nashville, TN | 2 Answers | 0 Votes Mark favorite Subscribe Comment
Assuming this: sqrt (e^9t) =e^t (e^9t)^(1/2) =e^t e^(9t/2) =e^t 9t/2 = t 9t/2 - t = 0 7t/2 = 0 t = 0 3/3/2014 | Steve S. Comment
√e^9t = e ^t e^(9/2)t = e^t The = should not be there , because it is only true for t =0 ln ( e^ (9t/2) = 9t/2 ln e ^t = t Maybe this was √e ^ 9t = e ^3 e ^ (9t/2) = e ^3 9t/2 = 3 t = 6/9 = 2/3 3/2/2014 | Parviz F. Comment